Human subcutaneous/ocular dirofilariasis in the Russian Federation and Belarus, 1997–2013 - Vladimir Kartashev; Tatiana Tverdokhlebova; Alla Korzan; Andrey Vedenkov; Luis Simón; Javier González-Miguel; Rodrigo Morchón; Mar Siles-Lucas; Fernando Simón (International Journal of Infectious Diseases, 2015)
Objectives: This study was performed to determine the yearly frequency, trends in spread, and clinical–epidemiological characteristics of human subcutaneous/ocular dirofilariasis (HSOD) in the Russian Federation and Belarus. Methods: The surveillance data of HSOD cases occurring between January 1997 and June 2013, obtained from the regional health administrations of the Russian Federation and Belarus, were analyzed. The spatial distribution of cases was assessed using a GIS map, and the clinical–epidemiological characteristics were defined using 719 cases for which information on anatomical location, age, sex, and area of residence was available. The statistical analysis was performed using the Chi-square test. Results: One thousand two hundred and seventy-two clinical cases of HSOD were identified, the majority of them reported in the south-western regions of the Russian Federation. The disease has spread into northern areas, changing its limit from latitude 45°N in 1997 to latitude 61°N in 2013. The statistical analysis of the data showed that the disease is more frequent in the ocular location, in women, in patients aged between 41 and 60 years, and in patients living in urban areas. Conclusions: Alternative sources to the scientific literature could be necessary to assess the epidemiological situation regarding HSOD in some areas where it has become an emerging condition. There is an urgent need for uniform criteria for reporting and retrieving human cases of dirofilariasis.